An introduction to quantum physics : a first course for physicists, chemists, materials scientists, and engineers /: a first course for physicists, chemists, materials scientists, and engineers. (2017) - Trachanas, Stephanos; Antonoyiannakis, Manolis; Tsetseris, Leonidas
No abstract available